Foreign Direct Investment, Conflict And Industrialisation In Africa - Sottie, J.O. (University Of Ghana, 2018)
This study set out to examine the effect of conflicts and FDI on industrialisation in Africa using a panel data on 48 African countries during the period 1980 to 2015. The African continent has been a typical recipient of FDI. FDI inflows are believed to boost economic growth and industrialisation, and for that reasons several African countries seek to attract FDI inflows. Theoretically, FDI inflows should boost industrialisation, especially FDI channelled to the manufacturing and industrial sectors by providing additional financial resources, technical expertise, and technology transfer amongst other benefits. Across the world, extant literature across provide mixed and inconclusive results on the effects of FDI inflows on industrialisation. This study sought to provide further evidence on the FDI-Industrialisation nexus in Africa using a more recent dataset, and to further examine the role of conflicts in the FDI-industrialisation nexus. The motivation for considering the potential role of conflicts stem from the fact that during the period 1980 to 2015, the African region experienced numerous incidences of civil wars which produced severe adverse effects on countries involved. Preliminary literature review suggested that civil wars significantly negatively affect economic development in countries that engage in it, and these adverse effects are pervasive and endure into the long term. To account for the effect of conflicts, the current study classified countries into conflict and non-conflict countries based on relevant and reliable data from multiple sources. A dummy variable was constructed to capture non-conflict countries. This variable takes the value of one (1) for those countries which did not experience civil wars during the period under study, and zero (0) for those countries which experienced civil wars during the same period. The study adapted industrialisation models used in extant literature. The main empirical estimations were run using the Feasible Generalised Least Squares (FGLS) technique under both the Common AR (1) and Panel-Specific AR (1) scenarios following results from diagnostic tests for autocorrelation, heteroscedasticity, multicolinearity and normal distribution. The estimations were subject to robustness checks by controlling for several relevant controls, and multiple estimation techniques such as the Prais-Winsten’s [common and panel-specific AR (1)], Pooled OLS, panel fixed effects and random effects techniques. The initial results from this study indicated that FDI had a negative significant effect on industrialisation in African countries during the period 1980 to 2015. This finding, seemingly lending support to the status quo, provided a motivation to explore whether conflicts could be an important variable in explaining this ‘paradox’ in the FDI-industrialisation nexus in Africa. In contributing to explaining the paradox in the FDI-industrialisation nexus, the study found sufficient evidence that FDI net inflows had a positive significant effect on industrialisation in non-conflict countries in Africa during the period 1980 to 2015. The study further found strong evidence that non-conflict countries experienced higher levels and faster pace of industrialisation than the conflict countries. The study concludes that the apparent evidence or prima facie evidence of negative significant effect of FDI net inflows on industrialisation observed in our preliminary results was due to the presence of conflict countries in the full sample. We therefore suggest that the negative significant effects or insignificant effects of FDI inflows on industrialisation observed in previous studies in Africa could be explained by the presence of conflict countries in the samples. We find that conflict or civil war is important in explaining industrialisation, and the FDI-industrialisation nexus in Africa. The study further shed light on the adverse effects of conflicts through the absorptive capacity hypothesis. Theoretically, conflicts destroy financial resources, human capital, infrastructure and systems which should provide countries with the required absorptive capacity to be able to channel FDI inflows into beneficial use to promote industrialisation. Periods of civil wars are associated with wastage, corruption, loss of human capital, loss of financial resources and destruction of infrastructure. Therefore for countries to benefit from FDI inflows in terms of boosting industrialisation, they should endeavour to eschew conflicts or civil wars. Other important findings were that manufacturing trade openness, per capita income and the financial sector were significant determinants of industrialisation in Africa during the period 1980 to 2015. Services productivity, government interventions and regulation did not have significant on industrialisation in African countries over the study period. Domestic investments had negative significant effect on industrialisation in African countries during the period 1980 to 2015, partly because large share of domestic investments were directed toward non-manufacturing sectors such as the natural resource sectors. It was also found that the agriculture productivity had a negative significant relationship with industrialisation. This finding suggests that the generally low levels and slower pace of industrialisation in Africa noticed from empirical works might be because most African countries are still agrarian economies. Thus large investments toward agriculture will boost agriculture productivity but slow down industrialisation, unless the investments in agriculture are directed toward agro-processing and production of intermediate inputs for industrial use. Thus policy makers should formulate and implement both medium-term and long-term industrial policies that seek to transform their economies from agrarian to industrial economies as they strive to promote industrialisation in the African region.
Keywords: Industrialisation; Investment; FDI-industrialisation